Los pasados de la memoria - Molina Jiménez, Iván (Editorial Universidad Nacional (EUNA), 2008)
An analysis of the origin of the existing explanations about the social reform promoted by the government of Rafael Ángel Calderón Guardia in Costa Rica from 1940-1943.